Study on the Vertical Stiffness of Bridge Expansion Joints Based on the Vehicle-Track-Bridge Coupled Model - Yunlu Wang; Mangmang Gao; Fei Yang (Shock and Vibration)
Bridge expansion joints (BEJs) are equipped at the girder end of long-span railway bridges to ensure the reliable transition of the track. BEJs should have suitable dynamic stiffness to ensure the running safety and stability of the vehicle. To explore the influence of dynamic vertical stiffness of BEJs on the dynamic response of vehicle, track, and bridge, a three-dimensional vehicle-track-bridge coupled model is established, and the influence of sleeper spacing and vehicle speed are taken into consideration. Taking a high-speed railway line in China as a case study, the dynamic response of the whole system is calculated. The results show that (1) the dynamic response of BEJs and the vehicle is affected by the vehicle speed and sleeper spacing. With the increase of vehicle speed and sleeper spacing, the dynamic response of the system increases; (2) the vertical stiffness of BEJs will affect the dynamic response of BEJs and the interaction between the wheel and rail: the vertical dynamic displacement of movable sleeper will exceed the limit if the vertical stiffness of pressure-bearing is insufficient, and the wheel unloading rate may exceed the limit if the vertical stiffness of the cushion plate is insufficient. Based on the results, the larger vertical stiffness of the cushion plate and pressure-bearing is recommended. These results have been applied to the design of BEJs on the studied railway line, which are in good service condition at present.